Performance Evaluation of HEBMO for Non-convex Economic Dispatch Problems Under Contingencies - Ismail N.L.; Musirin I.; Dahlan N.Y.; Mansor M.H.; Sentilkumar A.V.; Johari D. (Institute of Electrical and Electronics Engineers Inc., 2023)
Computer programming; Economic analysis; Electric industry; Electric power system economics; Evolutionary algorithms; Operating costs; Barnacle mating optimizer; Economic dispatch problems; Matings; Non-convex economic load dispatch; Nonconvex economic dispatches; Optimisations; Optimizers; Performances evaluation; Ramp rate limits; Reliability test system; Electric load dispatching